Thermal stability and activity improvements of a Ca‐independent α‐amylase from Bacillus subtilis CN7 by C‐terminal truncation and hexahistidine‐tag fusion. (26th February 2014) - Wang, Chenghua; Wang, Qingyan; Liao, Siming; He, Bingfang; Huang, Ribo
Abstract Simultaneous improvements of thermostability and activity of a Ca‐independent α‐amylase from Bacillus subtilis CN7 were achieved by C‐terminal truncation and his6‐tag fusion. C‐terminal truncation, which eliminates C‐terminal 194‐amino‐acid residues from the intact mature α‐amylase, raised the turnover number by 35% and increased the thermostability in terms of half‐life at 65 °C by threefold. A his6‐tag fusion at either the C‐ or N‐terminus of truncated α‐amylase further enhanced its turnover number by 59% and 37%, respectively. Molecular modeling revealed that these improvements could be attributed to structural rearrangement and reorientation of the catalytic residues.